2003
DOI: 10.1007/s00134-003-1778-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunoparalysis as a cause for invasive aspergillosis?

Abstract: Aspergillus infections are among the most feared opportunistic infections in humans. These organisms are ubiquitous in nature; protection against infection is usually provided by anatomical barriers and by the immune system. Tissue invasion by Aspergillus is uncommon, occurring primarily in the setting of immunosuppression. The prognosis of invasive aspergillosis is very poor. Although it is widely recognised that critically ill patients in the Intensive Care Unit (ICU) are at risk for nosocomial infections, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 19 publications
0
51
0
4
Order By: Relevance
“…He ve arkadaşları 17 da, kü-mülatif 350 mg ve üzerinde prednizolon kullanımının İPA riskini 8.6 kat artırdığını bildirmişledir. Çalışmamızda da, literatür 21 bilgileri ile paralel olarak, steroid kullanımının doza bağımlı olarak İPA gelişiminde etkili olduğu saptanmış ve yüksek olası İPA olgularında kümülatif steroid dozu 460 mg olarak belirlenmiştir.…”
Section: İstatistiksel Analizunclassified
“…He ve arkadaşları 17 da, kü-mülatif 350 mg ve üzerinde prednizolon kullanımının İPA riskini 8.6 kat artırdığını bildirmişledir. Çalışmamızda da, literatür 21 bilgileri ile paralel olarak, steroid kullanımının doza bağımlı olarak İPA gelişiminde etkili olduğu saptanmış ve yüksek olası İPA olgularında kümülatif steroid dozu 460 mg olarak belirlenmiştir.…”
Section: İstatistiksel Analizunclassified
“…A recent review of invasive fungal infections in critically ill patients with similar Simplified Acute Physiology Scores showed that aspergillosis was responsible for the highest crude mortality, of 63% [14]. Conditions associated with aspergillosis in these ''nonimmunosuppressed patients'' include chronic obstructive pulmonary disease (COPD), immunoparalysis secondary to sepsis, diabetes mellitus, chronic kidney disease, surgery, and steroid treatment [7,8,[15][16][17]. Our study population was characterized by diabetes, acute kidney injury requiring dialysis, ventilator dependency, malignant disease, trauma, underlying lung disease, and blood transfusion.…”
Section: Aspergillus Infections 209mentioning
confidence: 99%
“…When the latter reaction is excessive, it may lead to an immunoparalysis, also known as compensatory anti-inflammatory response syndrome. Consequently, the patient should be considered as temporarily immunocompromised and may be at risk of developing opportunistic infections, such as IPA [72].…”
Section: Pathophysiologymentioning
confidence: 99%